Radioactive iodine in low- to intermediate-risk papillary thyroid cancer - Zhao, Hengqiang; Gong, Yiping (Frontiers in Endocrinology, 2022)
It remains controversial whether papillary thyroid cancer (PTC) patients with low to intermediate risk disease should be performed with radioactive iodine (RAI) after total thyroidectomy (TT). We aim to identify those who might benefit from RAI treatment in PTC patients with cervical nodal metastasis after TT. Patients were divided into TT and TT+RAI groups from the SEER database (2004-2018). Overall survival (OS) and cancer-specific survival (CSS) were compared, and propensity score matching (PSM) was performed between groups. A total of 15179 patients were enrolled, including 3387 (22.3%) underwent TT, and 11792 (77.7%) receiving TT+RAI. The following characteristics were more likely to present with TT+RAI group: multifocality, capsular extension, T3, N1b, and more metastatic cervical lymph nodes. RAI was associated with better OS in low to intermediate risk PTC patients in the multivariate Cox regression model. The subgroup analysis showed that RAI predicted better OS in patients ≥ 55 years, AJCC stage II, and capsular extension with HR (95% CI) of 0.57 (0.45-0.72), 0.57 (0.45-0.72) and 0.68 (0.51-0.91), respectively. However, RAI failed to improve the prognoses of patients with age < 55 years, AJCC stage I, PTC ≤ 1cm, and capsular invasion. In the PSM cohort with 3385 paired patients, TT+RAI treatment predicted better OS compared with TT alone. In addition, TT+RAI predicted better OS in patients with metastatic cervical lymph nodes ≥ 2, multifocality, extracapsular extension and American Thyroid Association (ATA) intermediate risk. In conclusion, RAI was associated with better OS in low to intermediate risk PTC patients with age ≥ 55 years, multifocality, extrathyroidal extension and ATA intermediate risk. However, the survival benefit from RAI may be limited in patients with AJCC stage I, PTC ≤ 1cm, unifocality, capsular invasion and ATA low risk diseases even these patients showed pathological cervical lymph node metastasis.